The Use of Think Pair Share Technique to Improve Students’ Speaking Performance - Feni Cahyani (Universitas Syiah Kuala, 2018)
The aim of this research was to find out whether the use of Think Pair Share technique can improve students’ speaking performance or not. The writer uses Think Pair Share technique to teach speaking. Think Pair Share is a part of cooperative learning strategy that makes the students work together in small group. Quantitative method with experimental study of pretest and posttest control group design was undertaken in this research. The data result of the test was analyzed by using t-test. The result of the data analysis indicated that the students’ speaking score in experimental group after they taught by using Think Pair Share has been improved. The result of the data calculation showed that t-score was higher than t-table ( = 3.50 = 1.68) with the significant standard = 0.05 and the degree of freedom = 48. There are any improvements in students’ score in speaking performance after learning by Think Pair Share technique. In this case, Think Pair Share technique can be one of the teaching technique alternative applied by the English teacher in teaching English for English Foreign Language class.